REFLEKSI PENDIDIKAN AQIDAH DALAM PROBABILITAS PERMAINAN UNO: STUDI DI MAJELIS JAGONGAN AFWAJA DESA KALIBEBER KABUPATEN WONOSOBO - Nugroho Prasetya Adi; Zhul Fahmy Hasani; Robingun Suyud El Syam (SPESIFIK: Jurnal Pendidikan dan Pembelajaran, 2025)
Faith education is important to be connected to the reality of everyday life because faith is the foundation for living life, but the reality in the field has accommodated it little, so a review is needed to fill the gap. The article aims to reflect faith education in the probability of the UNO game. with a field setting at the AFWAJA Jagongan Assembly, Kalibeber Village, Wonosobo Regency. The study involved 30 correspondents synthesizing various articles that were relevant to the theme. The research concluded that in the UNO game, each player has an equal chance of winning each game. Probability here involves luck in drawing cards and the player's hand, and requires skill in choosing the right game. In statistics, probability is used to measure the degree of certainty or belief. The higher the probability of a particular event, the more likely the event is to occur. Probability is useful for making the right decisions, because life in the world is uncertain. In this context, uncertainty is not something to be avoided, but something to be understood and managed. In Islam, uncertainty is an opportunity that can be responded to with resignation, patience, prayer, and taking wisdom. This opportunity can be addressed by utilizing the potential that has been given by Allah SWT. This finding shows the importance of strong aqidah education which will provide a clear direction for every action of a Muslim, including in maintaining faith in Allah and ethics.